Planteamiento de una microempresa de venta de miel de abeja en el cantón Calvas, interpolando modelos de negocios relacionados - Merino Aguirre, Luis Fernando (2024)
The research focuses on applying the Systematic Literature Review method to analyze results on microenterprises selling honey in Ecuador, specifically in the case of Mielosos Apiculture. The objective is to propose a microbusiness model that satisfies the unmet demand for honey in the Calvas canton. The research, qualitative in its approach, offers a detailed understanding of the business characteristics of Mielosos Beekeeping, obtained through interviews, document analysis and observation. The results reveal that Mielosos Beekeeping lacks a structured and systematic agribusiness model, which affects its long-term sustainability. The need to abandon informal marketing and implement marketing strategies is highlighted, including changes in the product, distribution channel, advertising, and promotion. With these findings, a microbusiness model is proposed focused on the implementation of a business model for sales of bee products as the most efficient. Despite the limitation found in the scarce information in digital libraries, the proposal of the new model for Mielosos Beekeeping is presented as an exciting and sustainable opportunity. By focusing on responsible beekeeping practices and the production of high-quality honey, the model would not only strengthen the microenterprise's position in the market but could also contribute to economic development and environmental awareness in the Calvas canton. The successful implementation of this model would provide tools to improve the organizational structure, production and sale of the product, thus promoting a positive impact on the local community.